HISTORY AND DEVELOPMENT OF TAFSIR IN SOUTHEAST ASIA (Indonesia, Malaysia, Brunei Darussalam, Singapore and Thailand) - Amirulloh Sain Asari (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2016)
This paper describes the history and development of tafsir in Southeast Asia, namely Indonesia, Malaysia, Brunei Darusalam, Singapore and Thailand, aimed at providing a new discourse to the academic world, that Islam has another treasure in Far Asia, which is known as a pluralistic country because Islam entered in those countries without any wars. And to provide information related the books, author influence, and method of their tafsir in general.Keyword: History, Development Tafsir, and Southeast Asia